HEMPSEED AND COTTONSEED OILS IN THE ACCESSIONS FROM THE VIR COLLECTION AS SOURCES OF FUNCTIONAL FOOD INGREDIENTS - S. V. Grigoryev; T. V. Shelenga; K. V. Illarionova (Труды по прикладной ботанике, генетике и селекции)
Background. Oils of hemp and cotton presently have reduced retail trade offer in Russia, but are widely produced and used. Industrial hemp is still cultivated and processed domestically. In the 1950s, industrial cotton was cultivated on a hundred thousand hectares in the country, and now there are signs of its restored growing. Both crops have the ability to restore the raw material base to produce textile fibers, seed and oil as well as the potential to improve functional food production, because they contain functional food ingredients in their oil capable of reducing human nutrition disorder risks, preventing or restoring nutrient deficiencies, preserving and improving health.Materials and methods. Unsaturated and polyunsaturated fatty acids’ profiles of hempseed (Cannabis sativa L.) and cottonseed (Gossypium hirsutum L., G. herbaceum L., G. barbadense L.) oils were evaluated. Seeds were grown respectively under the conditions of the Russian North-West (hemp) and Adler District, Krasnodar Territory (cotton). The PUFA profile was measured using gas chromatography with mass spectrometry equipment (Agilent 6850, USA). All data were calculated using the UniChrom software.Results and conclusions. The content of the omega-6 linoleic acid in hemp accessions reached 64.2%; omega-3 alpha-linolenic acid, 27.1%; monounsaturated oleic acid, 14.0%. The sum of unsaturated acids was 94.2%; and that of polyunsaturated ones, 87.2%. Compared with hemp oil, cotton oil had a lesser sum of polyunsaturated (maximum 58.0%) acids, while its unsaturated acids were up to 79.0%. Oleic acid was found to reach 22.7% in cottonseed oil. Industrial cultivation of hemp and cotton in Russia need not be limited to textile fiber production, but may serve as a potential base of vegetable oils and food; just because of their PUFA contents, it is promising for the production of functional food ingredients, which have health benefits in reducing the risk of cancer and cardiovascular diseases, lowering the HDL cholesterol levels, and relaxing the smooth muscle cells in arteries, thus increasing the blood flow. Seed cake may be valuable addition to animal feed rations as well. As a result of the evaluations, valuable accessions (cultivars and lines) of hemp and cotton were identified. Although the selected accessions are not the products of previous breeding efforts aimed at the PUFA content improvement, they are promising source materials for the development of new cultivars with seeds enriched with compounds or sets of compounds that provide a beneficial effect on human health when included in the composition of food products (functional food ingredients).